Sequential extraction procedure of municipal solid waste incineration (MSWI) bottom ash targeting grain size and the amorphous fraction - C. De Matteis; L. Mantovani; M. Tribaudino; A. Bernasconi; E. Destefanis; C. Caviglia; S. Toller; E. Dinelli; V. Funari; V. Funari; V. Funari (Frontiers in Environmental Science, 2023)
Introduction: Bottom ash (BA) constitutes a significant by-product obtained during the incineration of municipal solid waste in waste-to-energy (WtE) plants. BA is a heterogeneous material made of different fractions, glass, minerals, metals, and unburned residual organic matter. Due to the non-hazardous nature of the unburned material, BA can be effectively recycled, becoming a valuable resource. However, BA displays a high content of potentially toxic elements (PTEs) within its finer grain size. The presence of these elements raises concerns regarding the potential toxicity associated with BA.Materials and methods: The release of PTEs in the smaller fraction (0.063–0.2 mm; 0.3–0.5 mm; 2–4 mm; bulk <4 mm) of BA collected from the Parma WtE plant was investigated using a new five-step sequential extraction procedure (SEP). Through this method, both leached solutions and solid residues were analyzed by inductively coupled plasma-mass spectroscopy (ICP-MS), X-ray powder diffraction (XRPD), and X-ray fluorescence (XRF) analysis. This integrated approach provided valuable insights into the mineralogy, chemical composition, and PTEs leachability of BA.Results and discussion: The novelty of this work is the development of a new SEP protocol specifically designed and planned for an anthropogenic material such as BA. The weight reduction recorded after each step is linked to the progressive disappearance of both crystalline and amorphous phases. Water-soluble phases, such as salts, are the first to react, followed by the carbonate fraction in the second step. At the end of the procedure, only quartz, corundum, and Ti-oxide are identified. Among the PTEs, Pb exhibits the highest release, particularly during the acid attack, followed by Zn. The significant release of Ni during the oxidizing and reducing steps can potentially be linked to hydroxides and metallic alloys, respectively. The integration of XRF and Rietveld refinement results on solid residues enabled the identification of several types of amorphous materials and their chemical evolution during the sequential extraction.